Influence of anthropometrics variables on the cardiorespiratory responses of children during exercise. - Fabiana Andrade Machado; Benedito Sérgio Denadai (Universidade Federal de Santa Catarina, 2011)
The objective of this study was to evaluate the influence of different body sizes on the cardiorespiratory responses of 10-13-year-old boys during the stages of a maximum-effortincremental test. Twenty boys underwent a continuous maximal incremental test on a cycle ergometer at an initial power output of 30 W and subsequent increases of 30 W at intervals of 3 min. Respiratory variables were assessed with a metabolic gas analyzer on a breath-by-breath basis. Heart rate was monitored continuously during the test. The groups were divided a posteriori according to maximal work output in the incremental test (90 or 120 W) and according to body weight (> 45 or < 45 kg). The following variables were continuously measured: respiratory frequency, tidal volume, ventilation, absolute and relative oxygen uptake, carbon dioxide production, heart rate, and ventilatory equivalent for oxygen. The anthropometric variables, especially height and body weight, were closely associated with the cardiorespiratory responses. These variables are limiting and determinant factors of performance and need to be included in the prescription and practice of physical exercise for this pediatric population.